Karakteristik Organoleptik dan Fisikokimia Bolen dengan Substitusi Tepung Bayam (Amaranthus Hybridus L.) - Kartika, Tati; Ningtias, Dinar Arum; Salma, Fitria Salsabila; Ulfuadah, Rachmawati Anisa; Alhazazie, Nauval; Nurtiana, Winda (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2025)
Bolen is a cake generally made from banana slices wrapped in a layer of wheat flour dough. Bolen with spinach flour substitute is one form of food product development which is expected to provide better nutritional content. The aim of this research is to determine the physicochemical and organoleptic characteristics of bolen products. This research used 4 formulations of wheat flour and amaranth flour, namely 96.67%: 3.33%; 95.34%:4.66%; 94%:6%; and 92.67%:7.33%. The results of the organoleptic analysis showed that the best bolen formulation was found in the wheat flour and spinach flour substitution treatment of 96.67% : 3.33%. The results of the analysis of the best product treatment were obtained on physical characteristics including product color parameters showing a lightness value (L*) of 50.25, a redness value (a*) of 2.02, and a yellowness value (b*) of 21.60, chroma and °hue values of 21.69 and 84.66 with a yellow red color range. Meanwhile, the texture results for the bolen product showed a peak value of 26.76 N. The chemical characteristic results included water content of 28.99%, ash 2.22%, protein 1.69%, fat 27.42%, and crude fiber 0.05%.